2012
DOI: 10.1080/09084282.2012.651951
|View full text |Cite
|
Sign up to set email alerts
|

Improving Test Interpretation for Detecting Executive Dysfunction in Adults and Older Adults: Prevalence of Low Scores on the Test of Verbal Conceptualization and Fluency

Abstract: Knowing the prevalence of low scores on a battery of executive-functioning tests supplements clinical interpretation and can reduce the likelihood of misdiagnosing deficits in executive functioning. The purpose of this study is to examine the base rates of low scores on the Test of Verbal Conceptualization and Fluency (TVCF; Reynolds & Horton, 2006 ) in healthy adults (n = 332; M (age) = 33.0 years, SD = 10.5, range = 20-59) and older adults (n = 138; M (age) = 74.9 years, SD = 7.8, range = 60-89) from the TVC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Our analyses showed that low scores are common in the healthy population. This finding is consistent with existing studies investigating this aspect of performance variability (Binder et al, 2009;Brooks et al, 2012;Palmer et al, 1998). According to Binder and colleagues (2009), a prevalence of low scores that falls ,20% is deemed uncommon, whereas a prevalence falling ,10% is unusual.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our analyses showed that low scores are common in the healthy population. This finding is consistent with existing studies investigating this aspect of performance variability (Binder et al, 2009;Brooks et al, 2012;Palmer et al, 1998). According to Binder and colleagues (2009), a prevalence of low scores that falls ,20% is deemed uncommon, whereas a prevalence falling ,10% is unusual.…”
Section: Discussionsupporting
confidence: 90%
“…The authors recommended that all test battery developers should provide information about the prevalence of variability in the general population. Using base rate tables of low scores supplements clinical interpretation and can help reduce the likelihood of misdiagnosis (also see Brooks, Iverson, Lanting, Horton, & Reynolds, 2012;Iverson, Holdnack, Brooks, & Lange, 2011). In this paper, information about low scores in a large normative sample of a comprehensive neuropsychological test battery will be provided.…”
mentioning
confidence: 99%
“…Research on multivariate base rates has illustrated and emphasized that when healthy people complete a battery of tests, a substantial minority will obtain one or more low scores (Axelrod & Wall, 2007;Binder, Iverson, & Brooks, 2009;Brooks, 2010Brooks, , 2011Brooks et al, 2011;Brooks, Iverson, Holdnack & Feldman, 2008;Brooks, Iverson, Lanting, Horton, & Reynolds, 2012;Brooks, Iverson, & White, 2007;Brooks, Strauss, Sherman, Iverson, & Slick, 2009;Crawford, Garthwaite, & Gault, 2007;Heaton, Grant, & Matthews, 1991;Heaton, Miller, Taylor, & Grant, 2004;Ingraham & Aiken, 1996;Iverson, Brooks, & Holdnack, 2008a;Iverson, Brooks, White, & Stern, 2008b;Palmer, Boone, Lesser, & Wohl, 1998;Schretlen, Testa, Winicki, Pearlson, & Gordon, 2008). This extensive line of research has provided clinicians with information for interpreting test performance in children, adults, and older adults on several large batteries of co-normed neuropsychological tests, including the Children's Memory Scale (CMS: Brooks, Iverson, Sherman, & Holdnack, 2009), the NEPSYÀSecond Edition (NEPSYÀII: Brooks, Sherman, & Iverson, 2010), the Expanded HalsteadÀReitan Neuropsychological Battery (EHRNB: see Table 4 in Binder et al, 2009; see Figure 9 in Heaton et al, 2004), the Neuropsychological Assessment Battery (NAB: Brooks et al, 2007;Brooks, Iverson, & White, 2009;Iverson et al, 2008b), the Test of Verbal Conceptualization and Fluency (TVCF: , the Wechsler Intelligence Scale for ChildrenÀFourth Edition (WISCÀIV: Brooks, 2010Brooks, , 2011, the Wechsler Adult Intelligence ScaleÀThird Edition/Wechsler Memory ScaleÀThird Edition co-normed battery (WAISÀIII/WMSÀIII: Iverson et al, 2008a), and the Wechsler Adult Intelligence ScaleÀFourth Edition/Wechsle...…”
Section: Research On Multivariate Base Ratesmentioning
confidence: 99%
“…There is now a large and mature body of evidence illustrating that when a battery of cognitive test scores are interpreted, it is common for healthy adults to obtain one or more unusually low scores (Brooks & Iverson, 2010;Brooks, Iverson, & White, 2009a;Brooks, Holdnack, & Iverson, 2011;Brooks et al, 2013;Iverson, Brooks, White, & Stern, 2008). Similarly, within a single domain of cognitive functioning, such as working memory (Brooks et al, 2013;Iverson, Brooks, & Holdnack, 2012), episodic memory (Brooks, Iverson, Holdnack, & Feldman, 2008;Brooks, Iverson, & White, 2007;Brooks et al, 2009a), executive functioning (Brooks, Iverson, Lanting, Horton, & Reynolds, 2012), and processing speed (Brooks et al, 2013;Iverson et al, 2012), a substantial minority of healthy adults and older adults will obtain one low score. The prevalence of low scores when simultaneously interpreting multiple scores is attributable to several factors, including: the number of scores being interpreted (e.g., there is a direct relation between the number of scores interpreted and the number of expected low scores or reliable change scores obtained); the cutoff score being used for interpretation (e.g., more lenient cutoff scores will produce more low scores or more reliable change scores); and the strength of the intercorrelations between the scores being considered (e.g., lower intercorrelations between tests will produce higher rates of low scores or higher rates of reliable change scores).…”
Section: Discussionmentioning
confidence: 99%